3D printed tricalcium phosphate-bioglass scaffold with gyroid structure enhance bone ingrowth in challenging bone defect treatment. (December 2021) - Zhu, Hao; Li, Meng; Huang, Xiaolong; Qi, Dahu; Nogueira, Liebert Parreiras; Yuan, Xi; Liu, Wenbin; Lei, Zehua; Jiang, Jiawei; Dai, Honglian; Xiao, Jun
Highlights: TCP/BG scaffold with gyroid structure was successfully and precisely manufactured using digital light processing method. Ideal mechanical properties and structural parameters were provided in the acquired TCP/BG scaffold with gyroid structure. TCP/BG scaffold with gyroid structure could effectively induce bone ingrowth and integration TCP/BG scaffold with gyroid structure could keep the surrounding trabeculae structure as natural. Abstract: Ceramic materials were applied to the area of bone defect treatment for a long time. The structure character and preparation method of ceramic scaffolds are of great importance to the satisfaction of defect repair. Among the myriads of forming methods, 3D printing technology allows to form porous and individualized ceramic scaffolds. Normally the extrusion-based 3D printing technique can only build scaffolds with grid structures, instead of complicated ones. In this study, the tricalcium phosphate/bioglass composite (TCP/BG) scaffold with gyroid structure was successfully and precisely manufactured using digital light processing (DLP) method. The surface characters, mechanical properties, and structural parameters of TCP/BG gyroid scaffold were analyzed. In vivo experiments demonstrated that compared to commercial artificial bone graft manufactured by conventional foaming method, TCP/BG scaffold with gyroid structure could effectively induce bone ingrowth and integration, meanwhile keep the surrounding trabeculae structure as natural. This kind of scaffolds presented great potential in the field of challenging bone defect treatment. Graphical abstract: Image, graphical abstract